INVESTIGASI FAKTOR AIR SEMEN RENCANA TERHADAP KINERJA BETON SEGARDAN KUAT TEKAN BETON SELF COMPACTING CONCRETE - Akhmad Suryadi; Qomariah Qomariah (Politeknik Negeri Malang, 2017)
Materials of concrete that is inseparable from modern social life. Concrete is used for the construction of roads, bridges, dams, power plants and buildings. The main constituents of concrete are cement, sand, gravel and water. With increasing concrete as a frequently used material, requires experts to make concrete with the latest technology by improving the quality of the concrete. With the existence of other material mixers, can be used as the latest technology in the manufacture of concrete, one of which is Self Compacting Concrete (SCC). The SCC concrete, is a concrete that can solidify itself. SCC concrete is a concrete that is done easily because the resulting mortar is very liquid compared with normal concrete. In this SCC concrete mixture, added with other ingredients in the form of admixture in the form of silicafume 5% of the weight of cement volume and the additive is fosroc 0.6% of the weight of cement volume. In the present study, it will be planned for a compressive strength of 35 MPa with a cylindrical test object. From the results of research on this SCC concrete is obtained slump flow results are eligible, with an average value of 60 cm with the standard value of slump flow with a value of 50 cm. While for testing L-Box test, the percentage value that has been fulfilled is at least 70% of the average height value of mortar in L-Box test tool. Obtained research value of 75%. For V-funnel test, this SCC concrete obtained qualified test result by passing V-funnel tool with standart duration for 8 seconds. Whereas the test that has been done obtained data duration for 5 seconds. While for the compressive strength of concrete produced is 15.01 MPa at 7 days. 20.24 MPa for 14 days old, while for 28 days old is 23.21 MPa. Can not meet the requirement or planned compressive strength that has been planned previously at 35 MPa.Keywords :Self Compacting Concrete, water cement ratio, fresh concrete, hard concrete